Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/dth.15313
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy for pediatric genital warts: A case report

Abstract: Genital warts (GWs) are the most common sexually transmitted infections (STIs), caused by the human papillomavirus. 1 The most common way of infection in adults is sexual, but transmission in pediatric populations remains controversial. 2 The increasing prevalence of GWs in children, ranged from 0% to 80%, 3 has renewed the interest in understanding the social and legal impact in cases of sexual abuse. In addition to concerns regarding the potential abuse, treatment for GWs in pediatric populations also presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…After a predetermined incubation period and upon irradiation with red light (~630 nm), these prodrugs stimulate cytotoxic reactive oxygen species (ROS) production, selectively destroying cells with a high metabolic state, including infective, tumoral, and inflammatory ones [31]. PDT has been used successfully in the treatment of non-melanoma skin cancer and actinic keratoses, with growing experience in the management of infectious dermatoses; however, less evidence exists for the treatment of inflammatory diseases, including NL [59][60][61][62][63]. The literature shows variable results about the efficacy of PDT, with clearance rates that are often very different from each other, with great variability between the number of sessions and the interval between sessions.…”
Section: Discussionmentioning
confidence: 99%
“…After a predetermined incubation period and upon irradiation with red light (~630 nm), these prodrugs stimulate cytotoxic reactive oxygen species (ROS) production, selectively destroying cells with a high metabolic state, including infective, tumoral, and inflammatory ones [31]. PDT has been used successfully in the treatment of non-melanoma skin cancer and actinic keratoses, with growing experience in the management of infectious dermatoses; however, less evidence exists for the treatment of inflammatory diseases, including NL [59][60][61][62][63]. The literature shows variable results about the efficacy of PDT, with clearance rates that are often very different from each other, with great variability between the number of sessions and the interval between sessions.…”
Section: Discussionmentioning
confidence: 99%
“…PDT, based on the topical application of 5-aminolevulinic acid (ALA) or its methylated ester (MAL) and irradiation with red light (approx. 630 nm), stimulates ROS production for the selective destruction of cells with a high metabolic state, including inflammatory, infectious, and cancerous ones, which explains its wide range of clinical applications [39][40][41][42][43][44]. Pooled data from three studies, with up to two treatments of red-light ALA-PDT, showed baseline lesion resolution rates of 89.1% and 32.7% at 12 weeks post-treatment for patients with AK administered ALA-PDT and placebo-PDT, respectively [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“… Macca et al (2022 ) proven the effectiveness of ALA-PDT on non-sexually transmitted genital warts of a 5-year-old female. They applied 10% ALA ointment and irradiated with red light after an incubation period of 3 h. At 3 months follow-up, only a few flat elements were still visible but after further 3 months complete clearance was detected.…”
Section: Pdt and Pediatric Infectious Skin Diseasesmentioning
confidence: 98%
“…Overall nine pediatric patients with genital viral warts were treated with ALA-PDT, achieving complete response in all cases (Xu et al, 2018;Macca et al, 2022). Xu et al (2018) reported eight treatment-resistant cases of pediatric genital warts successfully treated with 20% ALA-PDT.…”
Section: Genital Viral Wartsmentioning
confidence: 99%
See 1 more Smart Citation